Women Are Key for Future Growth : Evidence from Canada - Petersson, Bengt; Ishi, Kotaro; Mariscal, Rodrigo (Washington, D.C. : International Monetary Fund, 2017)
How important are female workers for economic growth? This paper presents empirical evidence that an increase in female labor force participation is positively associated with labor productivity growth. Using panel data for 10 Canadian provinces over 1990-2015, we found that a 1 percentage point increase in the labor force participation among women with high educational attainment would raise Canada's overall labor productivity growth by 0.2 to 0.3 percentage point a year. This suggests that if the current gap of 7 percentage points between male and female labor force participation with high educational attainment were eliminated, the level of real GDP could be about 4 percent higher today. The government has appropriately stepped up its efforts to improve gender equality, as part of its growth strategy. In particular, the government's plan to expand access to affordable child care is a positive step. However, we argue that to maximize the policy outcome given a budget constraint, provision of subsidized child care-including publicly funded child care spaces-should be better targeted to working parents.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet